Analisis Ragam Bahasa Gaul Yang Digunakan Remaja Milenial Pada Komentar Di Media Sosial Tiktok - Hasri Yulianti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This study aims to describe the use of millennial teen slang on Tiktok social media. This research is a descriptive qualitative research. Data collected using reading techniques, note-taking techniques and documentation techniques. The results showed that over time, more and more slang emerged that millennial teenagers used and the slang was used in their daily lives. Based on research, some slang used by teenagers on TikTok social media, namely Jakbar, Bumil, THR, Pulkam is a form of slang in the form of acronyms, kiyowo, server, spill, skincare is slang in the form of absorption and bet, thor, ka, merk is slang in the form of word fragments.